Control interno y su incidencia con la eficiencia operativa del banco Machala, sucursal Quevedo, año 2013 - Cedeño Aguirre, Yanina Lisseth (2015)
The examination was performed in Machala Bank Branch Quevedo, this investigation lasted 125 days, currently, the organization shows errors in internal control and procedures in organizational arrangement that does not allow them to effectively deploy each of scheduled tasks, for lack of a procedures manual, which makes the review, analysis, evaluation and monitoring of business processes developed by the bank. It should be noted that employees report that there is no address; they deny the mission, vision, objectives, strategies, policies, action plans and activities of the bank. Also Thus, according to the assessment of internal control and operational efficiency carried out by the bank, it was detected that: the absence of an analysis and planning prior within the entity, because you cannot not make an effective review, analysis, evaluation and monitoring of compliance with pre-planning within the institution for the development of operational efficiency, the lack of a management meeting schedule was detected and for this reason within the entity no proper organization for the various meetings. Therefore officials state that there is no proper addressing, unaware what the mission, vision, objectives, strategies and action plans within the entity.